The Public-Private Sector Wage Differential Across Gender in Italy: a New Quantile-Based Decomposition Approach - Castagnetti, Carolina; Rosti, Luisa; Töpfer, Marina (Economics Bulletin, 2019)
We use a novel approach that combines quantile wage gap decomposition to standard technique for panel regression.We apply this methodology to investigate the public sector wage gap throughout the wage distribution in Italy by gender. Controlling for unobserved (time-invariant) individual heterogeneity suggests no positive selection effect in the public sector. The analysis reveals a consistent public sector premium throughout the wage distribution and across gender independent from individual endowments (both observed and unobserved
Keywords: Gender